Determinants of Consumer Purchases in the Perspective of Business Psychology - Silvy Sondari Gadzali (CV. Media Digital Publikasi Indonesia, 2023)
Technology's quick advancement has compelled businesses to employ the most modern business practices, including e-commerce. However, a lot of businesses fail to take internal HR into account while aiming for company success. They believe that the machine is the key element. Since business goals are broad and include the welfare of many parties, the goal of this study is to examine the role of psychology in business. Because of this, it is crucial for a business to map the conceptual framework of consumer behavior using a variety of criteria. This is a library research project, and the data used is secondary data from various literatures. A qualitative descriptive method is used to assess the acquired data. According to the study's findings, business psychology is a field of study that examines how people behave in the workplace and approaches business from a human behavior perspective. Therefore, rather than machinery or manufacturing equipment, the function of humans in a firm or organization must be viewed as the primary factor in a business' success. Additionally, the application of psychology in business takes into account a number of elements that businesses must comprehend in order to draw in customers, at the very least through understanding their motivations, attitudes, and perception.